THE ROLE OF END-TO-END ANALYTICS IN DIGITAL MARKETING - Makhkamov, Azamat; Salimov, Oybek; Shokirov, Shirinbek (Science technology&Digital finance, 2023)
In our current scientific research, information is provided about the characteristics, types, advantages and components of digital marketing and why it cannot be effective without end-to-end analytics.